Menumbuhkan Karakter Qur’ani pada Anak Sejak Usia Dini - Aisyah, Siti Nur; Baqi, Safiruddin Al (Prosiding Lokakarya Pendidikan Islam Anak Usia Dini IAIN Ponorogo, 2022)
Qur'anic character education is an effort or direction by parents, teachers, or adults to instill excellent qualities in children's personalities based on the Qur'an and the Sunnah of the Prophet Muhammad by balancing knowledge, faith, morals, and charity. It is designed to enrich human life. Islamic principles surrounding Islamic teachings must be implanted in children's education from birth, because Islamic teachings are very essential and must be studied. If children acquire Islamic education from an early age, they will grow up to be human beings who love Allah and His Messenger and are loyal to their parents. The moral character of the Qur'an causes humans to be lifelong learners, capable of reading, comprehending, and applying the holy book of the Qur'an's positive principles in everyday life.